Preparation and Characterization of Enzyme Compartments in UV-Cured Polyurethane-Based Materials and Their Application in Enzymatic Reactions - Uhrich, Diana; von Langermann, Jan (Frontiers in Microbiology, 2017)
The preparation and characterization of UV-cured polyurethane-based materials for the mild inclusion immobilization of enzymes was investigated. Full curing of the polymer precursor/enzyme solution mixture was realized by a short irradiation with UV-light at ambient temperatures. The included aqueous enzyme solution remains highly dispersed in the polymer material with an even size distribution throughout the polymer material. The presented concept provides stable enzyme compartments which were applied for an alcohol dehydrogenase-catalyzed reduction reaction in organic solvents. Cofactor regeneration was achieved by a substrate-coupled approach via isopropanol or an enzyme-coupled approach by a glucose dehydrogenase. This reaction concept can also be used for a simultaneous application of contrary biocatalytic reaction conditions within an enzymatic cascade reaction. Independent polymer-based reaction compartments were provided for two incompatible enzymatic reaction systems (alcohol dehydrogenase and hydroxynitrile lyase), while the relevant reactants diffuse between the applied compartments.